Development of an Educational Application Using Gamification Approach: Peribahasa Pintar - Mazlan, Aina; Che Dalim, Che Samihah (Applied Information Technology And Computer Science, 2023)
The educational system is constantly evolving, and with the rise of nowadays technology, the integration of gamification in education can become increasingly popular. Students have difficulty remembering and comprehending a proverb since it has various interpretations. However, the proposed educational application’s gamified approach to learning can help students tackle this challenge by providing a fun and engaging way to learn proverbs and their meanings. The proposed educational application is designed to target children between the ages of 10-12 years old. Additionally, the application was developed using the Multimedia Mobile Content Development (MMCD) methodology, which ensured a comprehensive approach to creating engaging and interactive multimedia content. The app combines game elements and trivia to provide an immersive learning experience on Malay proverbs for children. With engaging features, kids effortlessly learn while having fun and participating actively. In Beta testing, the feedback showed 100% user acceptance, with users learning and remembering proverbs. Future work includes expanding content, adding awards, incentives, and social interaction.